2023
DOI: 10.3390/cancers15082206
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell Subsets in Melanoma: Pathophysiology, Clinical Prognosis and Therapeutic Exploitation

Abstract: Evasion from immunity is a hallmark of cancer development. Dendritic cells (DCs) are strategic immune cells shaping anti-tumor immune responses, but tumor cells exploit DC versatility to subvert their functions. Unveiling the puzzling role of DCs in the control of tumor development and mechanisms of tumor-induced DC hijacking is critical to optimize current therapies and to design future efficient immunotherapies for melanoma. Dendritic cells, crucially positioned at the center of anti-tumor immunity, represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 176 publications
0
3
0
Order By: Relevance
“…However, modulation by tumour cells may render them non-functional. 6 A retrospective study investigating immune-related gene signature and prognosis in melanoma patients, utilizing sequenced DNA data from 453 samples, reported that prognosis was negatively correlated with activated dendritic cell infiltration. 7 Furthermore, BRAF mutations are independently associated with worse overall survival since these mutations may gain treatment…”
Section: Nonmentioning
confidence: 99%
“…However, modulation by tumour cells may render them non-functional. 6 A retrospective study investigating immune-related gene signature and prognosis in melanoma patients, utilizing sequenced DNA data from 453 samples, reported that prognosis was negatively correlated with activated dendritic cell infiltration. 7 Furthermore, BRAF mutations are independently associated with worse overall survival since these mutations may gain treatment…”
Section: Nonmentioning
confidence: 99%
“…Recently, it has been proposed that pathological immune commitment begins with the first cells contacting and recognizing antigens [31][32][33]. Indeed, T-cell polarization could even be defined before antigen presentation when the microbial antigens induce a particular dendritic cell subset [31,[33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been proposed that pathological immune commitment begins with the first cells contacting and recognizing antigens [31][32][33]. Indeed, T-cell polarization could even be defined before antigen presentation when the microbial antigens induce a particular dendritic cell subset [31,[33][34][35]. Certainly, dendritic cells could selectively acquire particular functional characteristics by recognizing capsular antigens of P. gingivalis and consequently, could influence the polarization and function of T lymphocytes and the nature of periodontal immunity [28,29].…”
Section: Introductionmentioning
confidence: 99%